Measurement of hadron composition in charged jets from pp collisions with the ALICE experiment - Lu, Xianguo (Nuclear physics. A, Nuclear and hadronic physics, 2014)
We report the first measurement of charged pion, kaon and (anti-)proton production in jets from hadron colliders. The measurement was carried out with the ALICE detector using 2×108 minimum bias pp collisions at a centre-of-mass energy of s=7 TeV at the LHC. We present the π, K and p transverse momentum (pT) spectra, as well as the spectra of the reduced momentum (zch≡pTtrack/pT,jetch), in charged jets of pT between 5-20 GeV/c. The measurement is compared to Monte Carlo calculations.
Gesehen am 07.12.2020